A Brief Analysis Of Apology In Pondok Village, Padang, West Sumatera - hapsari, Astri (English Education Department, Universitas Islam Indonesia, 2013)
Communication by using spoken language cannot be separated from human's daily life. Every day, a person uses various utterances or illocutionary acts- part of speech acts, in order to communicate what he/she has in his/her thought to others. One may use the speech act to give a compliment, make a request, refuse an invitation, ask for an apology, etc. The knowledge required by an addresser (speaker) to perform illocutionary acts constitutes part of his/her communicative competence. An appropriate illocutionary act will be delivered if the addresser has a good communicative competence of his/ her language. Thus, in discourse studies of a language, it is important to set up units of analysis called speech act sets (Olshtain and Cohen, 1983). In this paper, the speech act set that will be discussed is the speech act set for apology. The community involved in this research is Chinese generation in Pondok Village, Padang, West Sumatera. The research is done in situ – the actual place where one can see people realistically in the language being studied. The aims of the research are to describe and analyze speech act set for apology as demonstrated by Chinese generation in Pondok Village, Padang, West Sumatera.Keywords: speech act set, apology, Chinese generation, Pondok Village, Padang, West Sumatera